解方程1、 (x-1)(x-2)分之2x-1=(x-2)(x-3)分之x-5 (2)2x平方-11x-21分之x=x平方-12x+35分之x+7(3)y平方-4分之2=y+2分之1-1 (4)x平方-4分之15+2-x分之2=1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 03:34:07
解方程1、(x-1)(x-2)分之2x-1=(x-2)(x-3)分之x-5(2)2x平方-11x-21分之x=x平方-12x+35分之x+7(3)y平方-4分之2=y+2分之1-1(4)x平方-4分之
解方程1、 (x-1)(x-2)分之2x-1=(x-2)(x-3)分之x-5 (2)2x平方-11x-21分之x=x平方-12x+35分之x+7(3)y平方-4分之2=y+2分之1-1 (4)x平方-4分之15+2-x分之2=1
解方程1、 (x-1)(x-2)分之2x-1=(x-2)(x-3)分之x-5 (2)2x平方-11x-21分之x=x平方-12x+35分之x+7
(3)y平方-4分之2=y+2分之1-1 (4)x平方-4分之15+2-x分之2=1
解方程1、 (x-1)(x-2)分之2x-1=(x-2)(x-3)分之x-5 (2)2x平方-11x-21分之x=x平方-12x+35分之x+7(3)y平方-4分之2=y+2分之1-1 (4)x平方-4分之15+2-x分之2=1
第一题
两边同乘于(y+2)(y-2),得
2=y-2-y^2+4
y^2-y=0
y(y-1)=0
解之得:y=0或y=1
第二题
两边同乘于(x+2)(X-2)
化简得 15-2(x+2)=x^2-4
x^2+2x-15=0
(x+5)(x-3)=0
解之得:x=-5或x=3
解方程2分之x+6分之x+12分之x+20分之x=1
解方程;x+2分之1+x分之1=x^2+2x分之32
x^2-2x分之4+x分之1=x-2分之2 解方程
解方程x+1分之x=x分之2-x+1分之1
解方程:x分之2+x+1分之6=x(x+1)分之15
x-1分之1=x分之2解方程
x-13分之x=2分之1 解方程
解方程;1-x分之(x)+1+x分之(x)+1+x平方分之2x+1+x四次方分之4x=0
解方程:x-2分之x减去x-6分之x-4等于x-1分之x+1减去x-5分之x-3等于多少
解方程:x-2分之x+x-7分之x-9=x-1分之x+1+x-6分之x-8
解方程x+2分之x+1+x+9分之x+8=x+3分之x+2+x+8分之x+7
解方程:x+1分之x+2加上x+4分之x+5等于x+2分之x+3加上x+3分之x+4
解方程x+2分之x+1-x+3分之x+2=x+6分之x+5-x+7分之x+6
解方程x+2分之x+1-x+3分之x+2=x+6分之x+5-x+7分之x+6
(x+2)分之(x+1)+(x+5)分之(x+4)=(x+3)分之(x+2)+(x+4)分之(x+3) 解这个方程
解方程 x+2分之x+3加x+3分之x+4=x+4分之x+5加x+1分之x+2
解方程:x+1分之x+2-x+3分之x+4=x+5分之x+6-x+7分之x+8
x+1分之x+2减去x+3分之x+4=x+5分之x+6减去X+7分之x+8 (解方程)